Penicillin Allergy Diagnostics by Specific IgE Study - Harvima, Rauno J.; Harvima, Ilkka T. (Medical Science: Trends and Innovations Vol. 5, 2025)
Aims: The aim of the study is to evaluate the allergic similarities between different penicillin forms and cefaclor. Study Design: Retrospective Laboratory Registry Data Analysis. Place and Duration of Study: Laboratory Registry Data obtained from the Central Laboratory of the Kuopio University Hospital District with a population of 251,000. Data collection between Jan 2010 and Aug 2021. Methodology: List of specific IgE analyses for phenoxymethylpenicillin, benzylpenicillin, amoxicillin and cefaclor with total serum IgE. Results: Penicillin forms of phenoxymethylpenicillin, benzylpenicillin, amoxicillin and cefaclor did not share the same antigenic determinants. Only 14 cases of formally positive specific IgE results were detected but setting the cut-off limit of specific IgE to 0.8 kU/L, then the number of positively-interpreted allergies dropped to 5 cases. Conclusion: We suggest that in case of suspicion of penicillin allergy, specific IgE analyses for phenoxymethylpenicillin, benzylpenicillin, amoxicillin and cefaclor with total serum IgE be performed for a better estimation of specific penicillin allergy. Previously recommended penicillin allergy testing by oral 250 mg amoxicillin is not a fully diagnostic test. Real IgE-mediated penicillin allergy is very rare.